Den røde fare: Politiovervågning af de danske kommunister og deres omgangskredse 1941-1943 - Nielsen, Jacob Vrist (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2025)
This article examines the Danish police’s surveillance of communists during the occupation years 1941-1943. Drawing on extensive archival research, it explores the methods and scope of both physical, postal, and electronic surveillance used to monitor communist networks. While the analysis highlights the limited eﬀectiveness of these eﬀorts, it also demonstrates how the surveillance of the communists served as a tool to expand state control over the Danish population. By analyzing previously underutilized sources, the article contributes new perspectives on a critical yet often overlooked period in Danish policing and occupation history.